Rural electrification in Africa – A willingness to pay assessment in Niger. (December 2020) - Bhandari, Ramchandra; Sessa, Vittorio; Adamou, Rabani
Abstract: About 84% of the population in Niger live in rural areas and only about 8% of them have access to electricity. For rural population, renewable energy use is an expensive option. This paper seeks to answer the question: Can collaborative consumption and community ownership increase the willingness to pay for the electricity generated through solar photovoltaics (PV) systems among the villagers of a rural area in Niger? Surveys were conducted in a rural village in Niger to assess the WTP for electricity services. These results were compared to the costs of off-grid electrification systems considering collaborative consumption and community ownership approaches. This was done by assessing the willingness to pay through household surveys and comparing the results to different electrification systems under the mentioned concepts. A reduction of about 80% monthly expenses could be achieved by using both collaborative consumption and community ownership. This translates to a possible increase in the WTP from 17% to 81% of the villagers for solar PV based electrification systems. Collaborative consumption, provided its acceptance and equipped with the proper policies and regulations, can thus contribute to a wider access to electricity in the rural areas of the country. Highlights: For a case study site in Niger, a field research combined with survey was carried out. Novel approach of collaborative consumption and ownership model was applied. A possible reduction of about 80% of the monthly energy costs can be achieved. The WTP in collaborative consumption operational model increased from 17% to 81%. Through demand side management, off grid renewables can be accommodated.